Cool outflows in MaNGA: a systematic study and comparison to the warm phase. Issue 3 (28th January 2022) - Avery, Charlotte R; Wuyts, Stijn; Förster Schreiber, Natascha M; Villforth, Carolin; Bertemes, Caroline; Hamer, Stephen L; Sharma, Raman; Toshikawa, Jun; Zhang, Junkai
ABSTRACT: This paper investigates the neutral gas phase of galactic winds via the Na i Dλλ5890, 5895Å feature within z ∼ 0.04 MaNGA galaxies and directly compares their incidence and strength to the ionized winds detected within the same parent sample. We find evidence for neutral outflows in 127 galaxies (∼5 per cent of the analysed line-emitting sample). Na I D winds are preferentially seen in galaxies with dustier central regions and both wind phases are more often found in systems with elevated star formation rate (SFR) surface densities, especially when there has been a recent upturn in the star formation activity according to the SFR_5 Myr/SFR_800 Myr parameter. We find the ionized outflow kinematics to be in line with what we measure in the neutral phase. This demonstrates that, despite their small contributions to the total outflow mass budget, there is value to collecting empirical measurements of the ionized wind phase to provide information on bulk motion in the outflow. Depending on dust corrections applied to the ionized gas diagnostics, the neutral phase has ∼1.2−1.8 dex higher mass outflow rates (M_out ), on average, compared to the ionized phase. We quantify scaling relations between M_out and the strengths of the physical wind drivers (SFR, L AGN ). Using a radial–azimuthal stacking method, and by considering inclination dependencies, we find results consistent with biconical outflows orthogonal to the disc plane. Our work complements other multiphase outflow studies in the literature that consider smaller samples, more extreme objects, or proceed via stacking of larger samples.